2017
DOI: 10.24059/olj.v21i3.1230
|View full text |Cite
|
Sign up to set email alerts
|

An Instructor Learning Analytics Implementation Model

Abstract: Abstract:With the widespread use of learning analytics (LA) tools, there is a need to explore how these technologies can be used to enhance teaching and learning. Little research has been conducted on what human processes are necessary to facilitate meaningful adoption of LA. The research problem is that there is a lack of evidence-based guidance on how instructors can effectively implement LA to support students. The goal of the study was to develop and validate a model to guide instructors in the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Participants found value in LA metrics that aligned with their unique pedagogical goals and how they used technology in their online course design to meet them. This finding affirmed studies elsewhere that described how educators sought ways to connect data to their pedagogical intentions (McKee, 2017;. Participant accounts described how their pedagogical knowledge allowed them to tie LA data to their course design.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Participants found value in LA metrics that aligned with their unique pedagogical goals and how they used technology in their online course design to meet them. This finding affirmed studies elsewhere that described how educators sought ways to connect data to their pedagogical intentions (McKee, 2017;. Participant accounts described how their pedagogical knowledge allowed them to tie LA data to their course design.…”
Section: Discussionsupporting
confidence: 75%
“…Wise and Jung (2019) found that faculty engaged in this reflection of their pedagogy alongside some of the more action-oriented sensemaking activities. Other studies have supported the use of LA for reflection (McKee, 2017;Q. Nguyen et al, 2018a).…”
Section: Pedagogical Responsesmentioning
confidence: 90%
See 1 more Smart Citation
“…When these technologies are in the control of teaching staff, rather than a Library team, teaching staff can determine how best to frame the inclusion of analytics as part of a subject's activity. This will be far more be effective in guiding the decision making of students as well as teachers (see McKee, 2017).…”
Section: Technologiesmentioning
confidence: 99%